2020
DOI: 10.3390/pathogens9060425
|View full text |Cite
|
Sign up to set email alerts
|

The Examination of Viral Characteristics of HIV-1 CRF07_BC and Its Potential Interaction with Extracellular Galectin-3

Abstract: HIV-1 CRF07_BC is a B’ and C subtype recombinant emerging virus and many of its viral characteristics remain unclear. Galectin-3 (Gal3) is a β-galactose binding lectin that has been reported as a pattern recognition receptor (PRR) and is known to mediate adhesion between cells and microbes. This study aims to examine the viral characteristics of HIV-1 CRF07_BC virus and the role of extracellular galectin-3 in HIV-1 CRF07_BC infection. A total of 28 HIV-1+ injecting drug users (IDUs) were recruited and 24 (85.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Increased serum galectin-3 has been observed in patients with varicella-zoster virus infection and patients with herpes zoster neuralgia and post-herpetic neuralgia presented with higher concentrations [17]. In human immunodeficiency virus infection, galectin-3 has been shown to support the attachment of the virus to macrophages and CD4+ T cells [19,34]. Galectin-3 was induced in hepatitis B and C infections [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased serum galectin-3 has been observed in patients with varicella-zoster virus infection and patients with herpes zoster neuralgia and post-herpetic neuralgia presented with higher concentrations [17]. In human immunodeficiency virus infection, galectin-3 has been shown to support the attachment of the virus to macrophages and CD4+ T cells [19,34]. Galectin-3 was induced in hepatitis B and C infections [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…A spectrum of complications observed in patients with coronavirus disease 2019 (COVID- 19) is not restricted to the widely recognized severe acute respiratory syndrome. The complications may include exacerbation of comorbidities, coagulopathies, bacterial superinfections with increased risk of sepsis, and multiple organ failure (MOF) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations at the Alix-binding site of the p6 region led to impaired HIV-1 replication and the decreased efficiency of viral budding in various cell types ( 12 ). A previous study revealed that the expression of Galectin-3 was upregulated in response to HIV-1 CRF07_BC infection ( 31 ), and the endogenous Galectin-3 facilitated the binding of Alix-Gag p6 complex to promote HIV-1 budding ( 32 ). However, this promoting effect could be disrupted because of the seven amino acid deletion in the Gag p6 region ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some cellular proteins have been reported to facilitate HIV virus replication, for example, galectin-3 (Gal3), a chimera type of the galectin family, exerting both endogenous and exogenous regulatory capabilities to various cellular immunol functions and even infectious status [ 36 , 37 ] ( Figure 1 B). The up-regulation of Gal3 was reported during HIV-1 infection by the Tat protein binding to the Gal3 expression promoter [ 38 ].…”
mentioning
confidence: 99%